Penciptaan Model Pembelajaran Bisnis Melalui Game “Chochorillo : The Lost Receipes” - Dhia Ayu Sabrina Soewandi (Journal of Animation and Games Studies, 2016)
Implementation of business education in the world of education is very important. However, many theories and teaching monotonous nature led to the knowledge of the business is difficult to be well understood. Thus, to introduce supply chain management as the business processes of an enterprise, it takes a learning method that is more innovative and creative as well as promoting business practices. One method of teaching that can address these problems is with education game business simulation genre. Chocorillo: The Lost Recipes is an educational game that teaches the business of business learning, especially concerning supply chain management which is packed with gameplay that is fun and exciting game story. This game there are 29 characters that the player can interact with them, doing quests from them, and resolve social problems that occur. The creation of this work is expected to generate business educational game that can provide learning effects without compromising the beauty aspect of the graphics so players do not get bored easily in use.Keywords: Android, game edukasi, bisnis, unity, supply chain management. AbstrakPenerapan pendidikan bisnis dalam dunia pendidikan merupakan hal yang sangat penting. Akan tetapi, banyaknya teori dan sifat pengajaran yang monoton menyebabkan pengetahuan akan bisnis sulit untuk dipahami dengan baik. Dengan demikian, untuk memperkenalkan supply chain management sebagai proses bisnis suatu perusahaan, dibutuhkan sebuah metode pembelajaran yang lebih inovatif dan kreatif serta mengedepankan praktik dalam bisnis. Salah satu metode pengajaran yang dapat menjawab permasalahan tersebut adalah dengan game edukasi bisnis bergenre simulasi. Chocorillo: The Lost Recipes merupakan game edukasi bisnis yang mengajarkan pembelajaran bisnis khususnya tentang supply chain management yang dikemas dengan gameplay yang menyenangkan dan game story yang menarik. Game ini terdapat 29 karakter yang pemain dapat berinteraksi dengan mereka, mengerjakan quest dari mereka, dan menyelesaikan permasalahan sosial yang terjadi. Penciptaan karya ini diharapkan dapat menghasilkan game edukasi bisnis yang dapat memberikan efek pembelajaran tanpa mengurangi aspek keindahan grafis sehingga pemain tidak mudah bosan dalam menggunakannya.Kata kunci: Android, game edukasi, bisnis, unity, supply chain management